EKOLOGI BUDAYA DALAM NOVEL DANUM KARYA ABROORZA A. YUSRA DAN IMPLEMENTASINYA TERHADAP PEMBELAJARAN SASTRA DI SEKOLAH - Melania Gultom; Eti Sunarsih; Gunta Wirawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to describe the cultural ecology in Danum novel by Abroorza A. Yusra using Julian Steward's perspective, namely: 1) describing the relationship between the environment and the use of technology and production in Danum novel by Abroorza A. Yusra, 2) describing the behavioural patterns of exploitation of the area related to technology in culture in Danum novel by Abroorza A. Yusra, 3) describing the relationship of the level of influence of the patterns of environmental utilization system on culture in Danum novel by Abroorza A. Yusra and, 4) describing the implementation of research results on literature learning in schools. This type of research is qualitative research with the data collection method using literature and note-taking techniques. The data analysis method used in this research is descriptive analysis technique. The results of the study explain that in the novel Danum: 1) the relationship between the environment and the use of technology in Danum novels is illustrated by the use of traditional technology such as nets, snares (bajang), machetes (iso hajok), spears and canoes in daily activities, 2) behaviour patterns of exploiting the area related to technology in Danum novels by the Dayak Uud Danum community include farming rice and rubber, hunting pigs, deer, other animals, looking for fish in the river, gathering, and looking for agarwood, 3) the influence of behavioural patterns of environmental utilization with other elements or aspects of the culture of the Dayak Uud Danum people in the Danum novel is shown in four aspects, namely the knowledge system, beliefs, arts, and language. 4) Implementation of the research results in the form of teaching modules in Senior High School class XII even semester with Learning Objective (LO) 12.5: Learners are able to read to assess and criticise characterisation and plot in narrative texts, as well as the authenticity of the depiction of society in novel texts.